Analisis Motivasi Belajar Mahasiswa Penerima Beasiswa di Program Studi Pendidikan Ekonomi FKIP Universitas Muhammadiyah Bengkulu - Rossa Ayuni; Ema Oktavia (Jurnal Multidisiplin Dehasen (MUDE), 2022)
This study aims to determine the learning motivation of Bank Indonesia Scholarship Recipients in the Economic Education Study Program, University of Muhammadiyah Bengkulu. This research uses descriptive, data and data sources of this research, namely primary data and secondary data. This data collection technique uses Observation, Interview, Documentation. There are 3 data analysis techniques, namely data reduction, data presentation, and conclusion drawing. The results of this study are the Learning Motivation of Scholarship Recipients at the Economic Education Study Program, University of Muhammadiyah Bengkulu using 6 indicators, namely the desire and desire to succeed to achieve success in carrying out tasks or work without procrastination, the encouragement and need in learning can avoid student failure in learning. doing assignments, having hopes and aspirations for the future in order to get high learning scores, always completing the assigned tasks so that hopes and dreams can be realized, rewards in learning can increase good learning motivation such as getting compliments, awards effectively, activities what is interesting in learning can motivate students to learn so that students become active in class, there is a conducive environment. Based on the results of interviews, it can be concluded that a student can study well and can generate motivation to learn to be more effective. effective in learning.